Upaya Peningkatan Kualitas Daging Ayam Broiler Melalui Pemberian Ekstrak Meniran - Puji Astuti; Heru Suripta; Lusia Risyani PM (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2017)
This research was conducted to evaluate the effects of extracts Phyllanthus niruri extracted with water and methanol as a substitute for commercial feed additive to determine the impact on the meat quality of broilers. The research use 200 broilers which were devided into four treatments and four replication: 1) Control, broilers were given drinking water without Phyllanthus niruri extract, 2) broilers were given feed additive commercially (bacitracin), 3) broilers were given methanol extract as much as 40 mg / l; and 4) broilers were given water extract as much as of 40 mg / l of drinking water. Each replication consisted of 10 broilers. At the end of the research, four broilers from each treatment were cut. The research used the completely randomized design. The variables observed were performance (feed intake, body weight gain and feed conversion), characteristics of the carcass (carcass percentage, meat and bone ratio, and percentage of abdominal fat), and the quality of the meat (fat, cholesterol, and unsaturated fatty acids). Data were analyzed variance analysis. The results showed that feed consumption (84,80 vs 89,31; 89,16; 9163 g/head/day), body weight gain (55,87 vs 59,57; 59,34; 59,70 g/head/day), carcass characteristics, and meat quality were influenced by Phyllanthus niruri extract. Water extracts provide better meat quality than the methanol extract.